RANCANG BANGUN GAME EDUKASI SEBAGAI MEDIA PEMBELAJARAN BERBASIS ANDROID MENGGUNAKAN ALGORITMA FISHER YATES - COMPUTING INFORMATIKA; Khilda Nistrina (Program Studi Teknik Informatika FTI UNIBBA, 2021)
Educational games can be one of the media for learning about cultural arts, as media in learning art and culture is desperately needed. But There are some issues, such as educators' incapacity to carry out learning in a creative and innovative, as well as educators' lack of expertise of how to use educational game-based learning media. Students are less familiar with arts and culture, particularly at SDN Sukasari 02, and there is a lack of student motivation in learning. The goal of this study is to create educational game applications in the arts and culture areas, as well as to demonstrate that educational games can be created on Android devices for educators and elementary school children at SDN Sukasari 02. The authors employed the R&D technique to create apps in this study. Unity 3D software and the C# (C Sharp) programming language are used to create applications and changing the order of questions presented to students at random using the Fisher Yates algorithm This study could aid educators in their teaching and learning efforts, as well as improve student interest in learning about the arts and culture.